La noción de la “mala vida” en la Revista Archivos de Psiquiatría, Criminología, Medicina Legal y Ciencias Afines, Buenos Aires (1902- 1913) en relación al Higienismo argentino - Mariana Angela Dovio (Nuevo mundo - Mundos Nuevos, 2012)
The objective of this study is to describe the use of the notion of low-life in the Archives of Psychiatry, Criminology, Legal Medicine and Related Sciences, a scientific review published in Buenos Aires during the early twentieth century. In this paper, we consider the notion of “low-life” as a category that may refer to a series of border behaviors as the crime and the insanity. In order to accomplish this research we analyses the role of Higienism and the discourses produced by the Buenos Aires Police through your Alienated Department Observation Service.